The Computation for the Fuzzy Subgroups of the Algebraic Structure D2> x C-z (2022)
Any finite uilpoleut group can be uniquely written as a direct product of /<- groups In this paper, an attempt for the compulation of Dv.i x CTi was made. This happens to be the eomputatioii of the number of distinct fuzzy subgroups of the cartesian product of the dihedral group of order 24 with a cyclic group of order sixteen